Cumulative dose γ-irradiation effects on material properties of AlGaN/GaN hetero-structures and electrical properties of HEMT devices. (22nd May 2019) - Sharma, Chandan; Visvkarma, Ajay Kumar; Laishram, Robert; Malik, Amit; Narang, Kapil; Vinayak, Seema; Singh, Rajendra
Abstract: The effects of γ -ray irradiation on AlGaN/GaN epitaxial layers and on high electron mobility transistor (HEMT) devices have been systematically investigated. The layer structure and HEMT device has been irradiated cumulatively with γ -ray dose of the order of 16 kGy. The x-ray diffraction (XRD) analysis of irradiated sample shows a lowering in full width at half maximum (FWHM) values along (102) and (002) planes in comparison to the pristine sample due to partial annealing effect. A decrease in the in-plane biaxial stress from 1.20 GPa to 0.75 GPa has been observed. Raman spectrum analysis also corroborates the reduction in stress post γ -ray irradiation. Edge dislocation density is reduced from 2.7 × 10 8 cm −2 to 1.75 × 10 8 cm −2 whereas the screw dislocation density remains almost unaffected. Further, Hall measurement shows an improvement in the mobility from 1580 cm 2 V −1 s −1 to 2070 cm 2 V −1 s −1 with reduction in sheet resistance. This improvement in mobility is attributed due to the decrease in surface roughness as confirmed by atomic force microscopy (AFM) characterization and also due to re-arrangement of the local defect centers as confirmed by cathodoluminescence (CL) imaging analysis. Finally, an increase in drain current from 99.5 mA mm −1 to 121.2 mA mm −1 with reduction in leakage current has been observed in case of HEMT device due to the improvement found in various material parameters.